2005
DOI: 10.1186/1476-069x-4-10
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of PCBs and chlorinated pesticides in pregnant women from Western Canada

Abstract: BackgroundMaternal exposures to organochlorines prior to pregnancy are considered a risk to neonatal welfare, specifically in relation to neurocognitive functions. There is growing interest in the evaluation of maternal blood testing as a marker for fetal exposure as well as the variable geographic distribution of these priority chemicals.MethodsThree hundred and twenty-three women in the second trimester of pregnancy entered the study at a prenatal clinic providing genetic counselling information. Subjects wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 30 publications
(22 reference statements)
4
19
0
Order By: Relevance
“…To this end, we believe our longitudinal cohort study is the first to provide empirical data regarding mean changes in serum concentrations of PCBs from the preconception-to-postnatal window of human development. A few previous investigators have assessed the stability of select PCB congeners across trimesters of clinically established pregnancies and reported them to be highly correlated (Longnecker et al 1999), as do investigators comparing maternal concentrations during established clinical pregnancies with cord or postnatal concentrations (Ayotte et al 2003; Jarrell et al 2005). However, such correlation coefficients cannot be adjusted for time intervals or other relevant covariates.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we believe our longitudinal cohort study is the first to provide empirical data regarding mean changes in serum concentrations of PCBs from the preconception-to-postnatal window of human development. A few previous investigators have assessed the stability of select PCB congeners across trimesters of clinically established pregnancies and reported them to be highly correlated (Longnecker et al 1999), as do investigators comparing maternal concentrations during established clinical pregnancies with cord or postnatal concentrations (Ayotte et al 2003; Jarrell et al 2005). However, such correlation coefficients cannot be adjusted for time intervals or other relevant covariates.…”
Section: Discussionmentioning
confidence: 99%
“…For research about pollutants in pregnant women it should be noted, because of different trends of POPs in each trimester of pregnancy [28, 29], the investigation of POPs within a pregnancy should be limited to one trimester for a more accurate evaluation. Meanwhile, previous studies reported that breastfeeding is one of the main routes for pollutants excretion [30, 31] and breastfeeding has a significant effect on decreasing the levels of organochlorine pesticides and PCBs in serum [32].…”
Section: Introductionmentioning
confidence: 99%
“…Anzalone et al Toxicology in Vitro 46 (2018) 39-46 the placenta (Foster et al, 2000;Jarrell et al, 2005). It is easier to discover some PCB metabolites than congeners (Gallenberg et al, 1990;Grimm et al, 2015).…”
Section: Sef Abnormal Cells (%)mentioning
confidence: 99%